2016
DOI: 10.4015/s1016237216500149
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation and Finite Element Analysis of the Maxillary Bone Injury Around Dental Implant During Chewing Different Food

Abstract: Since a long term patency of the dental implant has a direct relationship with their biomechanical performance, it is of vital important to understand the stresses and deformations that happen during chewing around the dental implant and bone. However, this model so far has not been well realized and this is why in this study we aim to establish a Finite Element (FE) model to analyse the stresses and deformations. A trajectory approach has been used to implement the action of muscles into the mode. To do this,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A 3D FE model of the human mandible was made according to our previous studies ( Karimi et al, 2014 , Razaghi et al, 2017 , Razaghi et al, 2016 ). Briefly, the solid models which were meshed with hexahedral elements consisted of the mandible bone, cortical and cancellous bones, PDL, pulp, dentine, enamel, and food (cornflakes bio) as displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3D FE model of the human mandible was made according to our previous studies ( Karimi et al, 2014 , Razaghi et al, 2017 , Razaghi et al, 2016 ). Briefly, the solid models which were meshed with hexahedral elements consisted of the mandible bone, cortical and cancellous bones, PDL, pulp, dentine, enamel, and food (cornflakes bio) as displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Having a realistic kinetic loading of the jaw system for movements such as chewing would help mimic the same pattern of motions that occurs during chewing in the mandibular system ( Hannam et al, 2008 ). This approach to measuring kinetic loadings, such as muscle force and trajectory ( Razaghi et al, 2017 , Razaghi et al, 2016 ), has been used in the recent publications of our group to mimic the kinetic loading of a jaw system during chewing. FEM models have been developed to calculate the stresses and deformations in the PDL under a combination of chewing and orthodontic ( Horina et al, 2018 ) or chewing only forces ( Martinez Choy et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of implant concepts and 3D printing technology, personalized root-shaped implants are gradually being noticed. Unlike conventional implant placement, personalized root-shaped implants do not require preparation for implant placement and mimic the biological behavior of natural teeth [47] . The biomechanical performance of the personalized root-shaped implant was studied by FEA, and it was found that the main set of stresses during inclined loading of the personalized root-shaped implant was located around the neck of the implant on the stressed side, and the stress maximum in the jawbone was located in the labial cortical bone region.…”
Section: Personalized Root-shaped Implantsmentioning
confidence: 99%
“…To obtain high computational precision, the tetrahedral element type was selected for the mandible, prosthetic bar, dental implant, abutment, and screw models. 27 According to the mesh convergence tests, 28 1.7-mm global edge length was specified for the tetrahedral element in the mandible models. For the dental implant, abutment, and screw meshing, 0.3-mm global edge length was chosen.…”
Section: Finite Element Analysismentioning
confidence: 99%